Hard/soft effects of multivalence co-dopants in correlation with their location in PZT ceramics. Issue 23 (1st December 2021) - Amarande, L.; Cioangher, M.C.; Toma, V.; Miclea, C.F.; Stefan, M.; Pasuk, I.; Iuga, A.R.; Negrila, C.; Matei, E.; Palici, A.M.; Joita, A.C.
Abstract: Piezoelectric hard/soft effects of multivalence co-dopants (Sb and Mn) in correlation with their location in the lattice, were investigated in PZT ceramics, prepared by conventional ceramic technology, with the following compositions: Pb0.98 Sr0.02 ((Ti0.49 Zr0.51 )1-0.015-x Mn0.015 Sbx )O3 with x = 0, 0.005, 0.01, 0.02, 0.03, where antimony was initially assumed to substitute for Ti/Zr ions. The antimony valence state was found to be +3 in all samples by X-ray Photoelectron Spectroscopy investigations. The Electron Paramagnetic Resonance spectra evidenced a steep enhancement of the Mn 2+ concentration upon increasing antimony doping level, explained by a charge compensation mechanism, between the Sb 3+ ions substituting Pb 2+ at the A-sites and the Mn 2+ ions, localized at the B-sites. The incorporation of Sb 3+ at the A-site of the PZT lattice is also supported by the variation of the lattice parameters, determined by X-ray Diffraction, with the increasing Sb concentration. The investigation of the dielectric, electromechanical and ferroelectric properties evidenced a hard piezoelectric behavior, mainly attributed to the presence of large sized Mn 2+ ions, localized at B-sites. Our results prove that the piezoelectric hard/soft response is decisively influenced by the interplay between multiple valence states and locations of the co-dopants, on one hand, and the charge compensation mechanisms, on the other hand. This provides indirect information about the location of some co-dopants which can substitute for both cationic sites in the PZT based ceramics.